Synthesis of (±)-Idarubicinone via Global Functionalization of Tetracene - Dennis, David G; Okumura, Mikiko; Sarlah, David (Journal of the American Chemical Society, 2019)
Anthracyclines are archetypal representatives of the tetracyclic type II polyketide natural products that are widely used in cancer chemotherapy. Although the synthesis of this class of compounds has been a subject of several investigations, all known approaches are based on annulations, relying on the union of properly prefunctionalized building blocks. Herein, we describe a conceptually different approach using a polynuclear arene as a starting template, ideally requiring only functional decorations to reach the desired target molecule. Specifically, tetracene was converted to (±)-idarubicinone, the aglycone of the FDA approved anthracycline idarubicin, through the judicious orchestration of Co- and Ru-catalyzed arene oxidation and arenophile-mediated dearomative hydroboration. Such a global functionalization strategy, the combination of site-selective arene and dearomative functionalization, provided the key anthracycline framework in five operations and enabled rapid and controlled access to (±)-idarubicinone.